Insert x + 3 instead of x into the equation of the function f(x):
f(x) = 3 - 6x²
f(x + 3) = 3 - 6(x + 3)²
use (a + b)² = a² + 2ab + b²
= 3 - 6(x² + 2(x)(3) + 3²) = 3 - 6(x² + 6x + 9)
use distributive property
= 3 + (-6)(x²) + (-6)(6x) + (-6)(9) = 3 - 6x² - 36x - 54
combine like terms
= -6x² - 36x - 51
<h3>Answer: f(x + 3) = -6x² - 36x - 51</h3>
Answer:
80.90
Step-by-step explanation:
15.83 ×7 =110.81
190.90-110.81= 80.09
Answer:
the first one
1, 2, 3, 4, 6, 9, 12, 18, 36
Answer: 1/3
Step-by-step explanation:
In advance I apologise if it is wrong